The Essentials of Computer Organization and Architecture / Second Edition - Lobur Julia; Null Linda (Jones And Bartlett Learning, 2006)
A comprehensive resource that addresses all of the necessary organization and architecture topics, yet is concise enough to cover in a single semester. Introduction, Data Representation in Computer Systems, Boolean Algebra and Digital Logic, An Introduction to a Simple Computer, A Closer Look at Instruction Set Architectures, Memory, Input/ Output and Storage Systems, System Software, Alternative Architectures, Topics in Embedded Systems, Performance Measurement and Analysis, Network Organization and Architecture, Selected Storage Systems and Interfaces, Data Structures and the Computer, Glossary, Answers and Hints for Selected Exercises, Index.